Physioxia enhances T-cell development ex vivo from human hematopoietic stem and progenitor cells. (15th August 2020) - Shin, Dong-Yeop; Huang, Xinxin; Gil, Chang-Hyun; Aljoufi, Arafat; Ropa, James; Broxmeyer, Hal E.
Abstract: Understanding physiologic T-cell development from hematopoietic stem (HSCs) and progenitor cells (HPCs) is essential for development of improved hematopoietic cell transplantation (HCT) and emerging T-cell therapies. Factors in the thymic niche, including Notch 1 receptor ligand, guide HSCs and HPCs through T-cell development in vitro. We report that physiologically relevant oxygen concentration (5% O2, physioxia), an important environmental thymic factor, promotes differentiation of cord blood CD34+ cells into progenitor T (proT) cells in serum-free and feeder-free culture system. This effect is enhanced by a potent reducing and antioxidant agent, ascorbic acid. Human CD34+ cell-derived proT cells in suspension cultures maturate into CD3+ T cells in an artificial thymic organoid (ATO) culture system more efficiently when maintained under physioxia, compared to ambient air. Low oxygen tension acts as a positive regulator of HSC commitment and HPC differentiation toward proT cells in the feeder-free culture system and for further maturation into T cells in the ATO. Culturing HSCs/HPCs in physioxia is an enhanced method of effective progenitor T and mature T-cell production ex vivo and may be of future use for HCT and T-cell immunotherapies. : Abstract : Thymic microenvironment in vivo is at low oxygen tension. Physioxia mimics the thymic atmospheric niche and enhances human cord blood HSC commitment and progenitor cell differentiation to progenitor/precursor T cells and maturation to T cells. Vitamin C mimics physioxia and intensifies effects of physioxia on T-cell development in serum- and feeder-free cultures and artificial thymic organoids.